Perhitungan Biaya Sewa Jaringan Distribusi pada Renewable Portfolio Standard Menggunakan Metode MVA-KM - Taufiq Indraputra Suharjono; Sasongko Pramono Hadi; Yusuf Susilo Wijoyo (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
The main problem of the implementation of Renewable Portfolio Standard (RPS) is due to its location away from the consumer. One solution to these problems is the implementation of the Pemanfaatan Bersama Jaringan Distribusi (PBJD). This study aims to analyze the economic aspects of the use of PBJD in the application of the RPS, the determination of the transmission cost. The cost allocation methods used in this paper are MVA-KM method and Unused Transmission Capacity method with Absolute, Reverse and Dominant approach.